2011
DOI: 10.1016/j.drudis.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Anglo-Saxon pharmacopoeia revisited: a potential treasure in drug discovery

Abstract: Modern translations provide a new opportunity to revisit the Anglo-Saxon medicinal texts, a valuable resource for discovering and developing novel compounds from native British flora. Previous pharmacological studies of 16 th and 17 th century medicinal plants reported in the Anglo-Saxon medical texts, suggest some were effective and led to the identification and isolation of new natural compounds such as matricin from Achillea millefolium L., a prodrug that yields chamazulene carboxylic acid, a natural profen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Along with the increasing application of clinical trial methodologies for the evaluation of traditional medicines for RA and other diseases, there has been increasing attention to the systematic assessment of the premodern and classical medical literature using text-mining approaches [20]. Such studies have focused on drug discovery from compounds found in the natural products used in traditional medicines [21][22][23]; identification of instances of long-term traditional use of natural products for certain diseases or symptoms [24][25][26][27]; the logic underlying ancient acupuncture prescriptions [28]; and investigations of continuities and differences between the classical and modern Chinese medicine approaches to certain diseases [29,30]. It has been proposed that long-term traditional use could be considered as a source of evidence [31], and a "whole-evidence" approach to evidencebased Chinese medicine could concludes systematic searching of the classical literature as one component [32].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the increasing application of clinical trial methodologies for the evaluation of traditional medicines for RA and other diseases, there has been increasing attention to the systematic assessment of the premodern and classical medical literature using text-mining approaches [20]. Such studies have focused on drug discovery from compounds found in the natural products used in traditional medicines [21][22][23]; identification of instances of long-term traditional use of natural products for certain diseases or symptoms [24][25][26][27]; the logic underlying ancient acupuncture prescriptions [28]; and investigations of continuities and differences between the classical and modern Chinese medicine approaches to certain diseases [29,30]. It has been proposed that long-term traditional use could be considered as a source of evidence [31], and a "whole-evidence" approach to evidencebased Chinese medicine could concludes systematic searching of the classical literature as one component [32].…”
Section: Introductionmentioning
confidence: 99%
“…Ancient Anglo-Saxon medicinal remedies have been receiving renewed scrutiny concerning their potential as rich sources of antibacterial compounds that could help combat modern drug-resistant bacterial infections [1]. As the discovery and development of novel antibiotics declines, the emergence of antibiotic resistant pathogens is an alarming threat to human health, with an estimated 700,000 deaths resulting from drug-resistant infections per year.…”
Section: Introductionmentioning
confidence: 99%
“…6 A number of drugs have originated from natural products used in traditional medicines. 7,8 A recent review reported that from 122 drugs derived from natural sources, 80% were developed for the same indication as their traditional use. 6 Some well-known drugs used for cough are derived from plant compounds, such as codeine from opium poppy (Papaver somniferum) and pseudoephedrine from Ephedra sinica.…”
Section: Introductionmentioning
confidence: 99%